Implementation Of Character Education Through The Implementation Of 5S Culture In Students At State Elementary School 232 Dampang - Uswatun Hasanah; Dyan Paramitha Darmayanti (Gudang Jurnal Multidisiplin Ilmu, 2026)
This anthropological study examines the implementation of the 5S culture (Senyum, Sapa, Salam, Sopan, Santun) as a mechanism for character education at State Elementary School 232 Dampang. Utilizing a qualitative ethnographic approach, this research investigates how daily cultural practices shape the moral values and behavioral patterns of students within the school ecosystem. Data were gathered through participant observation, in-depth interviews with teachers and students, and document analysis. The findings reveal that the 5S culture functions as a vital enculturation process, transforming abstract moral values into lived, daily habits. Teachers act as primary cultural models, fostering a respectful social environment. However, challenges persist, such as the social dissonance between the school's structured discipline and the students' varied external home environments. Ultimately, this study demonstrates that embedding repetitive cultural rituals within educational institutions effectively instills core values of empathy, respect, and social harmony, providing a sustainable model for early childhood character development.